Over Legislation Otorisasi Penegakan Hukum di Laut Indonesia - Teriyanti BTR; Jeihn Budiman (Penerbit Jurnal Indonesia, 2026)
This study aims to analyze the phenomenon of over legislation in the authorization of law enforcement at sea in Indonesia and its impact on the effectiveness of maritime law enforcement. Indonesia, as an archipelagic country with a vast maritime territory, has a high level of regulatory complexity, characterized by numerous laws and regulations and the involvement of various law enforcement agencies such as the Navy (TNI AL), BAKAMLA, POLAIRUD, the Ministry of Marine Affairs and Fisheries (KKP), Customs and Excise, and the Ministry of Transportation. This research employs a normative juridical method with conceptual, statutory, and comparative law approaches. The results of the study indicate that the characteristics of over legislation in maritime law enforcement in Indonesia include overlapping regulations, duplication of authority among institutions, weak coordination, the absence of a single leading sector, and complex case-handling procedures. These conditions result in legal uncertainty, inefficiency in supervision, conflicts of authority, a low deterrent effect on violations such as illegal fishing, and decreased trust from investors and international partners. This study recommends the need for codification of maritime security law through the establishment of an integrated Maritime Security Law, strengthening the role of BAKAMLA as the national coast guard, harmonizing sectoral regulations, and implementing the principles of good governance in the maritime law enforcement system to achieve legal certainty, effective supervision, and state sovereignty in Indonesia’s maritime territory.